Bridging the Digital Divide in Local Government: The Study of Internet Access and Digital Literacy in Nigeria Rural Area - AbuBakar, Hamisu Ibrahim (2012)
Internet access and digital literacy is still lagging in the rural communities of Garun-Malam local government and there are needs to investigate the reasons behind this unfortunate situation in order to overcome this digital handicap. Of course, good access to information technology (IT) is the fundamental element of any rural development activities. Therefore, this study focuses in depth the Internet access and digital literacy (in terms of Internet technology applications skills) in the rural areas of Garun-Malam local government in Kano State, Nigeria. The purpose of the study is to investigate accessibility level of the Internet (the technological infrastructures being used), and the level of Internet technology applications skills among the rural communities. Therefore, the study employs quantitative data analysis method, 150 questionnaires were distributed, collected and analyzed for the selected rural areas. From the results, it shows that many respondents have access to Internet, despite the fact that there are poor IT infrastructures used in all the rural communities. The study also reveals that majority of the respondents does not have basic skills of Internet technology applications. Furthermore, this study will usher a new era for its internal values and the results can be used by both State and local government. However, the outcome from this study may empower policy makers to makes decision/ suggestions in bridging the digital divide that exist in the rural area of Garun-Malam local government. Bridging the digital divide is such a need that requires immediate attention for any concerned government.